Comparative Analysis of the Effectiveness of the Topical Administration of Benzocaine and EMLA® on Oral Pain and Tactile Sensitivity - David Gomes de Alencar Gondim; Antonio Marcos Montagner; Ivo Cavalcante Pita-Neto; Romildo José de Siqueira Bringel; Francisco Aurelio Luchesi Sandrini; Eduardo Fernando Chaves Moreno; Amanda Mendes de Sousa; Andreza Bastos Correia (Hindawi Limited, 2018)
Objectives. To compare the effectiveness of the topical administration of benzocaine and EMLA on oral pain and tactile sensitivity. Materials and Methods. A randomized, double-blind, split-mouth clinical trial was carried out with 20 volunteers. The sensorial and quantitative tests were applied before the contact with topical anesthetic and after the application. Results. In the superficial tactile perception test, when we compared each group singly, there were statistically significant values in the decrease of superficial tactile perception when compared to the moment prior to the application of anesthetic agents. For the sensitivity to mechanical pain, no statistical significant difference was observed at evaluated times. In the needle penetration test, in an intergroup analysis, we found a decrease in the pain sensitivity to needle penetration at 5 min (p=0.053) and at 10 min (p=0.019) after the contact of the anesthetic drug with the oral mucosa. Conclusion. The application of topical anesthetic drugs reduces the discomfort associated with this procedure, mainly until the first 10 minutes. Only the needle penetration sensitivity test showed sufficient sensitivity to reveal a difference in the anesthetic effect between EMLA and benzocaine. This trial is registered with RBR-2N2GSW.